Estructura y gestión de la institucionalidad para el desarrollo del sector de los camélidos sudamericanos en Huancavelica entre el 2007 - 2012 - Quicaño Quispe, Isabel (2024)
The objective of this study is to analyze the type of public and private institutions for the development of the South American camelid sector in Huancavelica based on the transfer of functions and powers of CONACS as part of the decentralization process between 2007 and 2012; for which first, the process of transferring institutional functions and powers is described in itself; and second, the mechanisms used in inter-institutional coordination for the concerted management of development are presented. The methodology used was qualitative, to identify and analyze the interactions between public and private actors in the sector, and instruments such as documentary archive review were used, and semi-structured interviews were applied to 27 direct and indirect actors. The results show that there was a change in the type of institutionality for the development of the sector, which was weak and passive in relation to the previously generated institutionality. It was determined that the mechanism for transferring powers and functions during decentralization was purely administrative, without the participation of local actors, which generated institutional functional gaps, causing confusion due to the lack of definition of roles, loss of technical and material capabilities, division, competition between institutions promoting development and finally the coordination of public policies was annulled; Consequently, the interests of the camelid owners were postponed, abandoning them, exposing their weaknesses to the context and creating a feeling of permanent absence of the State.